The Role of Connectives and Stance Markers in the Processing of Subjective Causal Relations. Issue 8 (14th September 2021) - Wei, Yipu; Evers-Vermeul, Jacqueline; Sanders, Ted M.; Mak, Willem M.
ABSTRACT: Interpreting subjectivity in causal relations takes effort: Subjective, claim-argument relations are read slower than objective, cause-consequence relations. In an eye-tracking-while-reading experiment, we investigated whether connectives and stance markers can play a facilitative role. Sixty-five Chinese participants read sentences expressing a subjective causal relation, systematically varied in the use of stance markers (no, attitudinal, epistemic) in the first clause and connectives (neutral suoyi "so", subjective kejian "so") in the second clause. Results showed that processing subjectivity proceeds highly incrementally: The interplay of the subjectivity markers is visible as the sentence unfolds. Subjective connectives increased reading times, irrespective of the type of stance marker being used. Stance markers did, however, facilitate the processing of modal verbs in subjective relations. We conclude that processing subjectivity involves evaluating how the argument supports the claim and that connectives, modal verbs, and stance markers function as processing instructions that help readers achieve this evaluation.